Efektivitas Pelaksanaan Program Peningkatan Keselamatan Lalu Lintas Oleh Dinas Perhubungan Kota Padang - Restumy Amri; Desna Aromatica; Roni Ekha Putera (Universitas Lambung Mangkurat, 2020)
This research supports the design of a program to improve traffic safety by the Padang City Transportation Department. This program is an effort made by the Department of Transportation to replace the number of traffic accidents that are felt to be very high. Efforts in the future are directed at countermeasures that support efforts to foster, improve, regulate and enforce the law. This program is guided by Law Number 22 Year 2009 Concerning Traffic and Road Transportation Safety and Security Culture. This study used descriptive qualitative method. Data collection techniques used were interviews and documentation. The results showed how the implementation of the traffic safety improvement program conducted by the Padang City Transportation Office has not been going well. It can be seen from the meeting that the objectives of this program have not been successful because the number of accidents in the City of Padang has increased, the acquisition of resources in the implementation of this program has not well approved because the specified budget and human resources from the Padang City Transportation Office are still classified as inadequate because the demands from the Transportation Office are very large for the Padang City area. The internal process in the implementation program has been well approved in the process of communication between employees and a high commitment in managing transportation in the city of Padang. Strategic constituency satisfaction has not been well approved because it involves community participation in program implementation and self-safety.